Developing MOFI on Transverse Wave to Explore Studentsâ€™ Misconceptions Today: Utilizing Rasch Model Analysis - Shobrina Nurul Mufida; Ida Kaniawati; Achmad Samsudin; Endi Suhendi (Postgraduate, University of Mataram, 2022)
This research aimed to describe the diagnostic instrument validity from Multi-representation of Four-tier Instrument on Transverse Wave (MOFI-OTW), which is useful in exploring the misconceptions. The ADDIE (Analyzing, Designing, Developing, Implementing, and Evaluating) model has already been utilized as the research method. In the developing stage, item construction is in the form of multi-representation (statements, pictures, graphs, tables, and mathematical symbols). The sample consisted of 81 high school students aged 16-18 years (23 males called â€œCungâ€ and 58 females called â€œNdukâ€) in East Java. Data validity, instrument reliability, and distribution of students' conceptions have been analyzed using the Rasch Model with MINISTEP 4.7.0.0 software. Validity based on item dimensionality is valid. The reliability based on Cronbach Alpha (Î±) is good category, the value of item reliability is very good category, and person reliability is moderat category. Studentsâ€™ conceptions are categorized as Sound Understanding (SU), Partial Understanding Positive (PUP), Partial Understanding Negative (PUN), No Understanding (NU), Misconception (MC), and No Coding (NC). The largest conception category is MC. Misconceptions are still found in the sub-concept of transverse wave in various representations. In conclusion, MOFI-OTW can be developed through the ADDIE model by utilizing the Rasch analysis and used to explore students' conceptions and misconceptions.